Community Perception of the Development of Productive Landscape in Yogyakarta City - Raya, Alia Bihrajihant; Irwan, Siti Nurul Rofiqo; Utami, Retno Nur; Sarwadi, Ahmad (Universitas Sebelas Maret, 2020)
This research seeks to identify the potential of local community to support the development of productive landscape in Yogyakarta City. It hypothesizes the important roles of ecological perception, aesthetical perception, economics perception of productive plant, social-cultural perception, the role of social organization and the status of house ownership that would assist productive landscape development. This paper contributes to the importance of productive landscape development through community participation. The road/street location was chosen with purposive sampling by considering the characteristics of the arterial roads and local streets. Five arterial roads and five local streets were determined as the locations. The field survey method, with semi-structured questionnaires, was employed to obtain the primary data. The residences in arterial roads and local streets were selected by the linear systematic random sampling and the respondents participating in this study were 160 persons. The results have shown that the perception of residents depends on the experiences of their situation. The majority of residents have disclosed the low response on economical perception of productive landscape development in the greenery. The development of productive landscape is influenced by the ecological, aesthetical and socio-cultural perceptions of the residents living nearby the arterial roads. Meanwhile, the residents of local streets have a different perception of productive landscape development, which is influenced by ecological and aesthetical perceptions. The collaboration between government and community should be made to develop the efforts to grow and manage the vegetations along the roadsides of the city.